Improving the Effect of Calcined Salt Mud on Mechanical Properties of 3D Printing Materials Using Recycled Construction Aggregates - Yuntao Wang; Shangjin Jiang; Sudong Hua; Hongfei Yue; Yanan Zhang (Applied Sciences)
Using solid waste-based materials, such as recycled building aggregate (RCA), preparing 3D-printed materials can reduce costs but increase the water–cement ratio of the printed material, which reduces its mechanical performance. In order to solve the problem of mechanical properties decline caused by an increase in the w/c ratio, this experiment found that adding calcined salt mud (CSM) to the printing materials and changing the water-to-cement ratio from 0.37 to 0.4 CSM can ensure that the compressive strength of the printing materials remains basically unchanged. Moreover, through TG, SEM, and other microscopic data, it can be seen that calcium hydroxide in CSM can not only participate in the synergistic reaction of ethylene/vinyl acetate copolymer (EVA) and dust ash (DA), produce more NaOH, and promote the hydration of granulated blast furnace slag (GBFS) but also promote the formation of ettringite together with SO42− in solution, optimizing pore size distribution.